Application of the HIRADC Method for Hazard Risk Mitigation in Steel Pipe Manufacturing Processes - Aditya, Wulung; Hadi, Rachmat Yustiawan; Andrianto, Cayo Pungki; Aulady, Mohamad Ferdaus Noor (Journal of Civil Engineering, Planning and Design, 2025)
This study applies the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method to evaluate occupational health and safety (OHS) risks in the steel pipe manufacturing industry, specifically in machine installation and construction works performed by third-party contractors at PT. XYZ in East Java. These tasks are known for their elevated risk profiles due to limited supervision and differing OHS standards among contractors. The research adopts a qualitative approach through direct observation and interviews, analyzing risks using the ISO 45001:2018-aligned HIRADC framework. A total of 43 hazards were identified and initially categorized into 16 low, 20 medium, and 7 high-risk hazards. Following the implementation of control measures based on the hierarchy of controls (elimination, substitution, engineering, administrative controls, and PPE), risks were significantly reduced to 35 low and 8 medium-risk hazards. The findings highlight the effectiveness of systematic risk management and reinforce the need for continuous improvement in administrative and engineering controls. Regular evaluations are recommended to ensure the sustainability and responsiveness of the OHS system to evolving workplace conditions.